Kesan Simulasi Komputer Terhadap Pencapaian Dan Ketekalan Ingatan Pelajar Biologi Tingkatan Empat Bagi Topik Pembahagian Sel - Elangovan, Tavasuria (2014)
The purpose of this study was to evaluate the effectiveness of computer simulation such as realistic simulation and non-realistic simulation on Form Four Biology students’ achievement and memory retention for Cell Division topic. A quasi experimental study was carried out to identify the effectiveness of realistic simulation and non-realistic simulation on Form Four Biology students’ achievement, memory retention and student’s perception about realistic simulation and non-realistic simulation through a set of pre test and post test (post achievement test and post memory retention test). A set of questionnaire was also prepared to assess the student’s perception about the realistic simulation and non-realistic simulation for Cell Division topic. This study was conducted for six weeks with a sample of 136 Form Four Biology students in Perak, Malaysia from two secondary schools. All students were divided into treatment group (68 students) and control group (68 students). Biology classes were randomly selected for this study. First Biology class was randomly chosen as treatment group in which the students were taught with realistic simulation. Meanwhile, the second Biology class was chosen as control group in which the students were taught with non-realistic simulation Cell Division topic for three week. Pre test was given to the treatment group and control group students before they taught with realistic simulation and non-realistic simulation whereas post achievement test and questionnaire were given to the students after they learn Cell Division topic for three weeks.